Exploring the Dynamics of Character and Characterization on the Stage: A Comprehensive Analysis - Berdibaeva Altinay Keńesbaevna (Euro Asian Journal Publishing, 2023)
The realm of theatrical performance is a multifaceted tapestry where characters and their nuanced portrayals play a pivotal role in conveying the essence of a narrative. This scientific article delves into the intricate world of character and characterization on the stage, unraveling the significance of these elements in shaping the audience's perception and engagement with the theatrical experience. Drawing upon a synthesis of psychological, literary, and theatrical theories, this exploration aims to provide a comprehensive understanding of how characters are conceived, developed, and presented on stage.
Keywords: Character; Characterization; Theatre